Problematika Pembelajaran Matematika Berbasis Daring Pada Masa Pandemi Covid-19: Studi Kasus Kelas V SDN 22 Cakranegara - Setiawati, Putri Nur; A. Hari Witono; Muhammad Turmuzi (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
This study aims to identify and describe the dominant problems and problems in the implementation of online-based mathematics learning during the COVID-19 pandemic in grade 5 of SDN 22 Cakranegara in the 2020/2021 school year. This research was conducted in the grade 5 of SDN 22 Cakranegara. This type of research uses case study research with a descriptive qualitative approach. The research subjects in this study were teachers and students of class 5 SDN 22 Cakranegara. Data collection techniques are interview and documentation guidelines. The data analysis technique used is the interactive model of Miles and Huberman, through data collection, data reduction, data display, and verification/conclusion. The results showed that the problems in online-based mathematics learning were, among others: high internet quota, devices with unsupported memory, lack of focus on studying at home, difficulty understanding math material, and lack of independence of students in solving math problems. The dominant problem in the implementation of online-based mathematics learning during the COVID-19 pandemic is technical constraints, students often run out of quota and do not have their own cellphones. In the constraints of the learning process, students also experience several problems or obstacles including teacher explanations that are difficult to understand, lack of interest and motivation in participating in learning so that students feel bored when learning begins. As well as external constraints in the form of family economic difficulties that make it difficult for students to buy internet quotas.